(untitled) (Global Scientific Review, 2025)
This article analyzes the medical and social factors affecting women’s reproductive health during the Covid-19 pandemic. According to the World Health Organization (WHO), during the pandemic, healthcare systems were under excessive pressure, which created serious challenges in ensuring women’s sexual and reproductive rights. The study found that women’s reproductive health is closely related to economic, social, and demographic factors, and that during the Covid-19 pandemic, their lifestyle, psychological state, sexual activity, and overall health were significantly influenced by stress factors.